In vitro activities of ceftriaxone and fusidic acid against 13 isolates of Coxiella burnetii, determined using the shell vial assay. - Torres, H (1993)
The susceptibilities of 13 isolates of Coxiella burnetii to fusidic acid and ceftriaxone were determined by use of the recently described shell vial assay (D. Raoult, H. Torres, and M. Drancourt, Antimicrob. Agents Chemother, 35:2070-2077, 1991). At a concentration of 4 micrograms/ml, ceftriaxone was bacteriostatic for four isolates and slowed the multiplication of the other nine. Fusidic acid at a concentration of 2 micrograms/ml was bacteriostatic for six isolates and slowed the multiplication of three others. These results show that these compounds could be effective in the phagolysosome of C. burnetii-infected cells.